Severe traumatic injury is associated with profound changes in DNA methylation - Trine O. Eskesen; Kristian Almstrup; Laurits Elgaard; Tobias Arleth; Mathilde L. Lassen; Andreas Creutzburg; Alice Herrlin Jensen; Niklas Breindahl; Felicia Dinesen; Malene Vang; Erik Sørensen; Anders Wallin Paulsen; et al. (npj Genomic Medicine, 2024)
Abstract Whether DNA methylation changes follow human physical trauma is uncertain. We aimed to investigate if severe trauma was associated with DNA methylation changes. In a prospective, observational, clinical study, we included severely injured adults and adults undergoing elective surgery (controls). Blood was obtained from trauma patients (n = 60) immediately- and 30-45 days post-trauma, and from surgical patients (n = 57) pre-, post-, and 30-45 days post-surgery. Epigenome-wide DNA methylation profiling was performed and analyzed for significant differentially methylated CpGs and -regions (DMRs) within and between groups. Within the trauma group we identified 10,126 significant differentially methylated CpGs and 1169 DMRs. No significant differential methylation was found in the surgical group. In the trauma group, differentially methylated sites were enriched in genes and pathways involved in blood coagulation and inflammatory response. Severe trauma was associated with profound alterations in the DNA methylome of circulating leucocytes, and differential methylation was located in trauma-relevant genes.